Slaves, Spices and Ivory in Zanzibar Integration of an East African Commercial Empire into the World Economy, 1770-1873. - Sheriff, Abdul (Eastern African studies., 1987)
Abdul Sheriff analyses the early stages of the underdevelopment of East Africa.